Depression: Cognition Relations after Stroke. Issue 6 (August 2015) - Hommel, Marc; Carey, Leeanne; Jaillard, Assia
Background: Poststroke depression and cognitive dysfunction are common and are independent predictors of poor recovery. Aims: We assessed whether and how depression and cognition were correlated in the subacute period after stroke. Method: We prospectively recruited 207 nondemented patients (Mini Mental State Examination ≥ 23) presenting with a first-ever ischemic stroke (127 males), mean age of 48·5 years (16·4 standard deviation), median 12 days after infarction, as assessed on magnetic resonance imaging. We administered a comprehensive neuropsychological battery involving cognitive domains including instrumental functions, memory, executive functions, and working memory. Depression was quantified with the Beck Depression Inventory. Results: Depression (Beck Depression Inventory > 9) was identified in 30·4% of the patients (95% confidence interval 24·2–37·2%). Median Beck Depression Inventory was 6. Median Mini Mental State Examination was 30. Cognitive dysfunctioning in at least one neuropsychological test was present in 89% (95% confidence interval 84–93%). Each point increase of Beck Depression Inventory was associated with an odd of 1·1 (95% confidence interval 1·04–1·19) of changing to a worse category of cognition. Stroke location was not correlated with depression. All cognitive domains were significantly correlated with depression. In multivariate analysis, the executive functions ( P = 0·001) and the working memory ( P = 0·009) were the best predictors of depression when adjusted for demographic and stroke characteristics. Conclusions: The rates of depression and cognitive impairment were in the range of previous stroke studies. Our study suggested a strong relation between depression and cognition characterized by executive functions and working memory dysfunctioning.